2020
DOI: 10.1002/bab.1846
|View full text |Cite
|
Sign up to set email alerts
|

Decolorization and degradation potential of enhanced lignocellulolytic enzymes production by Pleurotus eryngii using cherry waste from industry

Abstract: Lignocellulosic wastes accumulate in large quantities and thus cause environmental issues. Cherry waste (CW) of them collected from industry was used as the substrate to increase production of lignocellulolytic enzymes, laccase (Lac), manganese peroxidase (MnP), lignin peroxidase (LiP), carboxymethyl cellulase (CmCase), xylanase, exoglucanase, β-glucosidase (BGLA), by Pleurotus eryngii. Then, the decolorizations of some azo dyes were examined. The effects of different concentrations of some compounds, such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…Many factors affect the secretion of lignocellulolytic enzyme production by fungi, such as the fermentation method, the type and complexity of carbon and nitrogen sources, ion concentration, temperature, and more (Stajić et al 2006;Sohail et al 2009;Zhang et al 2013;Bentil et al 2018;Ferraz et al 2019;Filipe et al 2019;Akpinar and Urek 2020;Rajavat et al 2020). The types of substrates and the mode of cultivation of fungal species play an essential role in enzyme productivity.…”
Section: Introductionmentioning
confidence: 99%
“…Many factors affect the secretion of lignocellulolytic enzyme production by fungi, such as the fermentation method, the type and complexity of carbon and nitrogen sources, ion concentration, temperature, and more (Stajić et al 2006;Sohail et al 2009;Zhang et al 2013;Bentil et al 2018;Ferraz et al 2019;Filipe et al 2019;Akpinar and Urek 2020;Rajavat et al 2020). The types of substrates and the mode of cultivation of fungal species play an essential role in enzyme productivity.…”
Section: Introductionmentioning
confidence: 99%
“…Results showed that colour removal was positively correlated with the presence of Iron in the textile wastewater samples (ρ = 0.77, p-value = 0.041). Iron, together with Copper, have been already reported to induce the enzymatic activities correlated to colour removal of cherry waste by in Pleurotus eringii [63].…”
Section: Fungi Bioassaysmentioning
confidence: 99%
“…The review envisions the improvement of the activity of DyPs against lignin to reach satisfactory conversion levels for industrial applications. In line with the requirements for sustainable scale‐up, Akpinar and Urek [7] used cherry waste collected from industry as substrate and Pleurotus eryngii as the microorganism to increase production of lignocellulolytic enzymes such as laccase (Lac), manganese peroxidase, lignin peroxidase, carboxymethyl cellulase, xylanase, exoglucanase, and β‐glucosidase. The data show that P. eryngii adapted to all solid‐state fermentation conditions and resulted in increased enzymatic activities that also demonstrated decolorizing performance.…”
Section: New Enzymatic Technologies For the Modification Of Lignocellmentioning
confidence: 99%